Qualitative and quantitative investigations on the macrobenthic fauna of Central Amazon lakes. I. Lago Tupe, a black water lake on the lower Rio Negro - Reiss, Friedrich (Amazoniana, 1977)
Lago Tupé is a black water "ria lake". It is connected with the Rio Negro throughout the year and shows similarly large fluctuations in water level, amounting to nearly 8 m in 1971. The exceptionally high minimum water level of thê one-year sampling period implied that there was thermal stratification in the lake throughout the year; because of this the oxygen content of the bottom water layers did not exceed 0,6 mg/l, and H2S formed in the hypolimnion during the period of decreasing wafer level.
Keywords: Lago Tupé